A Research on Individual Social Responsibility and Social Entrepreneurship Tendencies of University Students - Ugur Sonmezoglu (Journal of Educational Issues, 2024)
The aim of this research is to examine the individual social responsibility and social entrepreneurship levels of university students in terms of some variables and to examine the effects of individual social responsibility levels on their social entrepreneurship orientations. Relational survey model, one of the quantitative research methods, was used in the research. The study group of the research consists of 200 students who study in sports sciences at universities in Turkey. SPSS statistical program was used in the analysis of the data. First, descriptive statistics were examined, and parametric tests were used for inferential statistics. In addition, Independent Samples t Test, Pearson correlation analysis and simple linear regression analysis were performed. When the research findings are evaluated, the fact that students have been involved in a social project before, except for the sub-dimension of financial return, has social entrepreneurship orientations and individual social responsibility levels; Taking the community service practice course has a positive effect on the development of their individual social responsibility levels and their social vision from the dimension of social entrepreneurship. In addition, it has been revealed that university students’ whether they do sports or not has no effect on their individual social responsibility and social entrepreneurship. It has been revealed that as the individual social responsibility levels of recent students increase, their social entrepreneurship orientations also increase, and individual social responsibility has a positive effect on social vision, innovation, sustainability, and social networks in social entrepreneurship sub-dimensions.